Wilma Tenderfoot : the case of the putrid poison - Kennedy, Emma, 1967- (Kennedy, Emma, 1967- Wilma Tenderfoot, 2011)
As apprentice detective to Theodore Goodman, Wilma, a ten-year-old orphan of Cooper Island's Lowside Institute for Woeful Children, helps investigate who is poisoning actors at the Valiant Vaudeville Theater but when Theodore disappears, she must take action on her own.